Cell-Associated Human Immunodeficiency Virus (HIV) Ribonucleic Acid Has a Circadian Cycle in Males With HIV on Antiretroviral Therapy. (16th October 2021) - Stern, Jared; Solomon, Ajantha; Dantanarayana, Ashanti; Pascoe, Rachel; Reynaldi, Arnold; Davenport, Miles P; Milush, Jeffrey; Deeks, Steven G; Hartogensis, Wendy; Hecht, Frederick M; Cockerham, Leslie; Roche, Michael; et al.
Abstract: Background: Circadian transcription factors that regulate cell-autonomous circadian clocks can also increase human immunodeficiency virus (HIV) transcription in vitro. We aimed to determine whether circadian variation in HIV transcription exists in people with HIV (PWH) on antiretroviral therapy (ART). Methods: We performed a prospective observational study of male PWH on ART, sampling blood every 4 hours for 24 hours. Using quantitative polymerase chain reaction, we quantified expression of circadian-associated genes, HIV deoxyribonucleic acid (DNA), and cell-associated unspliced (CA-US) ribonucleic acid (RNA) in peripheral blood CD4+ T cells. Plasma sex hormones were quantified alongside plasma and salivary cortisol. The primary outcome was to identify temporal variations in CA-US HIV RNA using a linear mixed-effect regression framework and maximum likelihood estimation. Results: Salivary and plasma cortisol, and circadian genes including Clock, Bmal1, and Per3, varied with a circadian rhythm. Cell-associated unspliced HIV RNA and the ratio of CA-US HIV RNA/DNA in CD4+ T cells also demonstrated circadian variations, with no variation in HIV DNA. Circulating estradiol was highly predictive of CA-US HIV RNA variation in vivo. Conclusions: Cell-associated unspliced HIV RNA in PWH on ART varies temporally with a circadian rhythm. These findings have implications for the design of clinical trials and biomarkers to assess HIV cure interventions. Abstract : Despite suppressive antiretroviral therapy, males with HIV display a circadian cycling in cell-associated HIV RNA, having implications on the design of cure trials such as sampling and intervention times. Circadian cycles offer a novel target for latency reversal.